2019
DOI: 10.1371/journal.pone.0223731
|View full text |Cite
|
Sign up to set email alerts
|

Inter-method and anatomical correlates of episodic memory tests in the Alzheimer’s Disease spectrum

Abstract: BackgroundEpisodic memory impairments have been described as initial clinical findings in the Alzheimer’s Disease (AD) spectrum, which could be associated with the presence of early hippocampal dysfunction. However, correlates between performances in neuropsychological tests and hippocampal volumes in AD were inconclusive in the literature. Divergent methods to assess episodic memory have been depicted as a major source of heterogeneity across studies.MethodsWe examined correlates among performances in three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(62 reference statements)
0
3
1
Order By: Relevance
“…We found such a relation in our MCI subgroup for all segmentation methods, but not in the cognitively normal or AD groups. These results contrasted with previous reported relationships in AD between the delayed subtest of RAVLT with HOC in a Brazilian sample (Sudo et al 2019) and with HCvol within ADNI (X. Wang et al 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…We found such a relation in our MCI subgroup for all segmentation methods, but not in the cognitively normal or AD groups. These results contrasted with previous reported relationships in AD between the delayed subtest of RAVLT with HOC in a Brazilian sample (Sudo et al 2019) and with HCvol within ADNI (X. Wang et al 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…It is universally known that episodic memory is the first cognitive domain involved in the AD spectrum and the most sensitive neuropsychological indicator for early AD (Dubois et al, 2007). The AD pattern of gray matter was found in SCD which correlated with episodic memory decline (Peter et al, 2014), and RAVLT demonstrated significant association with the Hippocampal Occupancy Score and hippocampal volumes in the AD spectrum (Sudo et al, 2019). However, the change of hippocampus tends to be asymmetry in SCD, and the structural MRI studies revealed a decreased volume preferred the right hippocampus (Yue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most widely used and accessible imaging methods, it is currently recommended in diagnostic criteria for AD (Jack et al, 2018). T1‐ and T2‐weighted images show different atrophy patterns and white matter alterations across different dementia syndromes (Harper et al, 2017), which all correlate with degree of the cognitive impairment (Bayram et al, 2018; Sudo et al, 2019; Wolk & Dickerson, 2011). The 7T MRI can provide further information about cognitive decline at an ultrahigh resolution, such as hippocampal subfield changes across dementias and MCI (McKiernan & OBrien, 2017).…”
Section: Discussionmentioning
confidence: 99%